1983
DOI: 10.1104/pp.73.2.304
|View full text |Cite
|
Sign up to set email alerts
|

Invertase Activity and the Kinetin-Stimulated Enlargement of Detached Radish Cotyledons

Abstract: Cytokinin treatment is known to promote expansion of light-grown excised radish (Raphanus sativus L. cv Crimson Giant) cotyledons. This expansion, at least in part, seems to be related to an increased accumulation of osmotically active reducing sugars. Kinetin treatment did not cause increased levels of isocitrate lyase activity over the controls, but stimulated increased levels of two invertase forms, designated types I and II. Type I was soluble and type II was insoluble after homogenization in 10 millimolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…As cell enlargement declines, the concentration of hexose decreases and Suc increases. It is not clear in these studies whether acid invertase promotes cell expansion energetically (Ricardo and ap Rees, 1970) or through increased osmotically active sugars (Howard and Witham, 1983).…”
Section: Higher Suc Composition Results In Smaller Fruit Sizementioning
confidence: 99%
“…As cell enlargement declines, the concentration of hexose decreases and Suc increases. It is not clear in these studies whether acid invertase promotes cell expansion energetically (Ricardo and ap Rees, 1970) or through increased osmotically active sugars (Howard and Witham, 1983).…”
Section: Higher Suc Composition Results In Smaller Fruit Sizementioning
confidence: 99%
“…Cytokinins also inhibited invertase synthesis in sugar cane stem segments, but its effects were unspecific [7] . Cytokinins promote expansion in excised, light-grown radish cotyledons [27] and this expansion is associated with an increase in the concentration of reducing sugars [20] and a rise in acid invertase activity [ 19] .…”
Section: Cytokininsmentioning
confidence: 99%
“…In a number of systems the stimulation of growth and acid invertase activity by exogenous growth regulators is prevented by prior or simultaneous treatment with inhibitors of mRNA or protein synthesis [11,46,23,24,40 ;Morris and Arthur,unpublished] . Several authors have suggested that de novo synthesis of invertase may occur in response to growth regulator treatments [46,24,19] . Detailed studies of acid invertase synthesis in sugar cane stem tissues led to the conclusion that both GA 3 and auxins (IAA and NAA) stimulated synthesis of the enzyme by stabilizing pre-formed invertase mRNA [7, 111 . However, other claims for de novo initiation of invertase synthesis by growth regulators require more rigorous examination .…”
Section: Control Of Enzyme Turnovermentioning
confidence: 99%
“…This adduces support to the ohservation of Levitt (1980) that stressed plants respond more to BAP than unstressed plants. The enhancement of pollen germination and tube growth by BAP is possibly due to its effect on the enhanced incorporation of amino acids into proteins under saline conditions (Kahane & Poljakoff-Mayber, 1968;Singh & Singh, 1980) or to the increased invertase activity in pollen which would provide precursors for pollen tube wall synthesis as reported for chicory roots (Rutherford & Bard, 1971) and radish cotyledons (Howard & Witham, 1983).…”
Section: Discussionmentioning
confidence: 96%